An Investigation Study of Thinning Distribution in Single Point Incremental Forming Using FEM Analysis - Qasim Mohamed Doss (Al-Khwarizmi College of Engineering – University of Baghdad, 2013)
Single Point Incremental Forming (SPIF) is a forming technique of sheet material based on layered manufacturing principles. The sheet part is locally deformed through horizontal slices. The moving locus of forming tool (called as toolpath) in these slices constructed to the finished part was performed by the CNC technology. The toolpath was created directly from CAD model of final product. The forming tool is a Ball-end forming tool, which was moved along the toolpath while the edges of sheet material were clamped rigidly on fixture.